Keyphrase Extraction Model: A New Design and Application on Tourism Information (Informatica, 2021)
Keyphrase extraction has recently become a foundation for developing digital library applications, especially in semantic information retrieval techniques. From that context, in this paper, a keyphrase extraction model was formulated in terms of Natural Language Processing, applied explicitly in extracting information and searching techniques in tourism. The proposed process includes collecting and processing data from tourism sources such as Tripadvisor.com, Agoda.com, and vietnam-guide.com. Then, the raw data was analyzed and pre-processed with labeling keyphrase and fed data forward to Pretrained BERT model and Bidirectional Long Short-Term Memory with Conditional Random Field. The model performed the combination of Bidirectional Long Short-Term Memory with Conditional Random Field in order to solve keyphrase extraction tasks. Furthermore, the model integrated the Elasticsearch technique to enhance performance and time of looking up tourism destinations' information. The outcome extracted key phrases produce high accuracy and can be applied for extraction problems and textual content summaries.